The value of publishing official central bank forecasts - Juha Tarkka; David Mayes (Bank of Finland, 1999)
The aim of the present analysis is to shed light on the question whether Central Banks should publish their macroeconomic forecasts, and what could possibly be gained in monetary policy if they did so.We show that disclosing the Central Bank's assessment of the prevailing inflationary pressures in the form of a forecast improves macroeconomic performance even if this assessment is imprecise.This is because it makes policy more predictable.We are also interested in finding out the useful content of the forecasts, if published, and answering the question whether it makes a difference if these official forecasts are "unconditional" in the sense of incorporating the Central Bank's forecasts of its own policy as well, or "conditional" on some other policy assumption. Possible conditional alternatives may include assuming unchanged instruments, however specified, or assuming the kind of policy that the private sector is estimated to expect.The analysis comes out in favour of publishing unconditional forecasts, which reveal the intended results of monetary policy.A discussion of some practical issues related to publishing official macroeconomic forecasts is also provided.
URN:NBN:fi:bof-20140807658
Keywords: 330; forecasting; transparency; monetary policy; central banks